Impact of ventricular pacing modalities and pacing percentage on new-onset atrial fibrillation after dual-chamber pacemaker implantation - Zhang, Meng; Xu, Jian; Wang, Jianhua; Liu, Yuxin; Jin, Yuyang; Li, Shufeng; Cao, Wei (Frontiers in Cardiovascular Medicine, 2025)
ObjectiveTo investigate the impact of the ventricular pacing modalities and ventricular pacing percentage (VP) on the incidence of new-onset atrial fibrillation (AF) following dual-chamber pacemaker implantation. We aim to explore how these factors, along with left atrial diameter (LAD), contribute to AF development, providing insights into optimizing pacemaker settings to potentially reduce AF risk in pacemaker patients.MethodsBetween January 1, 2020, and December 31, 2022, a total of 371 patients who underwent initial dual-chamber pacemaker implantation at the Second Affiliated Hospital of Harbin Medical University were enrolled. These patients were categorized into two groups: the non-AF group and the AF group, based on the presence of new-onset AF during one-year follow-up. Regular remote follow-up visits were conducted postoperatively, with endpoint events defined as the detection of AF. A comparative analysis was performed to evaluate the differences in basic characteristics, implantation site of the ventricular lead, and pacemaker programming settings between the two groups.ResultsThe AF group exhibited a significantly higher prevalence of hypertension and a greater proportion of left bundle branch pacing (LBBP) compared to the non-AF group. Additionally, the AF group had a lower proportion of patients with ventricular pacing (VP) in the 0%–39% range, but a higher proportion of patients in the 40%–79% range. Notably, the LBBP cohort demonstrated a significantly lower incidence of AF. The AF group also presented with a larger left atrial diameter (LAD). Multivariate analysis revealed that LBBP and VP in the 0%–39% range were independently associated with a reduced risk of new-onset atrial fibrillation AF. Among the predictive indicators for new-onset AF, both LBBP and LAD demonstrated notable sensitivity and specificity.ConclusionsVentricular pacing modalities and percentage significantly impact new-onset AF after dual-chamber pacemaker implantation. LBBP and lower VP percentages are associated with a lower risk of AF development, whereas a larger LAD may be linked to an increased likelihood of its onset. Optimizing these factors could potentially reduce the risk of AF in pacemaker patients.